The Role of Physical Evidence and Empathy in Influencing Patient Visit Rates at Hialu Health Center, North Konawe - Arafah, Muhammad; Sunarsih, Sunarsih; Asri, Andi (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction: The number of patient visits to the Hialu Health Center continues to increase with an average number of patient visits in 2021 of 225 visits per month. This study was conducted at the Hialu Health Center, Landawe District, North Konawe Regency. The purpose of this study was to analyze the Relationship between Physical Evidence and Empathy to the Level of Patient Visits at the Hialu Health Center, Landawe District, North Konawe Regency. Method: This study uses a quantitative method with a comparative research design. The population of the entire Landawe District community is 2,843 people and a sample of 351 using the Slovin formula. Result: Based on the linearity test between variables, the variables of physical evidence and empathy generally have an effect on the level of patient visits to the Hialu Health Center, Landawe District, North Konawe Regency. Conclusion: The relevant government, especially the Health Service, must continue to provide easy access for the Hiau Health Center to improve health facilities and infrastructure in order to provide more optimal health services to the community.